The Comparison of Ketorolac, Paracetamol and Pethidine on Postoperative Pain Control for Outpatient Transurethral Lithotripsy - Mehryar Taghavi Gilani; Majid Razavi; Alireza Bameshki; Arash Peivandi Yazdi (Tehran University of Medical Sciences, 2023)
Background and Aim: Treatment of acute postoperative pain is one of the most important measures to improve recovery. Different methods of local and regional anesthesia, and also numerous intravenous drugs have been used.  In this study, the analgesic effect ketorolac, paracetamol and pethidine in the postoperative pain control of outpatient transurethral lithotripsy was evaluated. Materials and Methods: This clinical trial was performed on 96 patients who were candidates for outpatient transurethral lithotripsy in Mashhad Imam Reza Hospital. In randomized double blinded study, at the end of the operation, 30 mg of intravenous ketorolac to the first group, 1 gram paracetamol in half an hour to the second group and 50 mg of pethidine to the third group were injected. Pain was assessed every 10 minutes to half an hour and then, every half an hour to 4 hours by numerical rating scale (NRS). Finally, the data were analyzed by SPSS v16 software. The relationship between quantitative variables was analyzed by analysis of variance and the qualitative variables was assessed by Chi-square test and P<0.05 was considered significant. Results: There was no significant difference between three groups in demographic information. The pain intensity in the first 10 minutes after surgery was the same between the groups (P=0.372), but the pain intensity at 20, 30 and 60 minutes after surgery was significantly different in the three groups (P.values ​​0.005, 006, and 0.001 respectively), and was lower in the pethidine group. In other hours after surgery, no significant difference in pain control was observed between the three groups. The need for additional analgesia was higher in the paracetamol group than in the other two groups (P=0.025) in the first hour. Hemodynamic changes and surgical complications such as nausea and vomiting were the same in both groups. Conclusion: The present study showed that pethidine causes better pain relief than ketorolac and paracetamol in the first hour after surgery, but after 60 minutes there is no significant difference between these three groups.